One patient's experiences and expectations in the healthcare system: Complicated and critical illness with rare diagnosis described by his advocate - Jennifer Cademartori (The Beryl Institute, 2019)
The health care business serves as a profession in the art of human illness. But unlike other businesses there is the human side, the patient experience. These patients are the “customers” receiving the care, but they, unlike customers at a retail store, are vulnerable and scared and must trust their lives in the hands of people they don’t know. The paradigm must change to reflect how the health care business is handled from the eyes of the person receiving the care from the first office visit, through the inpatient stay, to follow up visits. Patient focused training on all levels with the goal of seamless healthcare from phone to discharge to future visits to reach Value Based Health Care will help empower healthcare professionals and meet the expectations of patients [Lateef 2011]. As a health care provider for 25 years I have witnessed health care from a support staff perspective to a bedside RN to a Nurse Practitioner caring for complicated inpatients and outpatients. But the greatest learning curve for me was that as the wife of a complicated patient, my husband.